Success Attribution and Support for Income Equality: Evidence from the United States and Germany - Bai, Xinyi (International Journal of Global Economics and Management, 2024)
Income inequality within countries is a pressing global issue, and understanding its determinants is crucial for informing policies aimed at fostering economic fairness. In this paper, we use individual data from World Values Survey (WVS) wave 7 data (2017-2022) to study how the attribution of success to different (luck or effort) factors affects the views on income distribution (specifically, whether to support income equality or inequality). Our main hypothesis is that attributing success to effort rather than luck leads to a larger and statistically significant increase in the acceptance of inequality in the indulgent country – the United States. We indeed find that attributing success to effort is significantly and positively correlated with supporting income inequality in the United States, while this correlation is significantly weaker in Germany. But from the regression results, the country does not significantly change the relationship between success attribution and supporting income equality. Therefore, we reject our main hypothesis and conclude luck rather than effort as the source of success can’t lead to a more substantial and statistically significant increase in support in income equality in indulgent countries.